Sanksi Pidana terhadap Pengasuh Tempat Penitipan Anak terhadap Kematian Anak yang Diasuh - Gede Made Agus Paramartha; I Ketut Sukadana; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2020)
Children are one of the gifts entrusted by God Almighty to every parent. They have the obligation to supervise and maintain the development of each child. Children should also be cared for properly by their parents, but it is not uncommon for children to be cared for by others through child care services. When a child is under supervision at a child care service, there is negligence by the caregiver which causes the death of the child. Based on this background, this study aimed to describe how the legal protection for children who are left in a child care center and what are the criminal sanctions for the caregivers of child care center toward child deaths. This research was conducted using the normative legal method. The results of this study showed that children who are left in a child care center get legal protection to prevent children from getting acts that threaten the child's psyche. Legal protection is specifically regulated in Law Number 35 of 2014 concerning child protection. In addition, the criminal sanction for caregivers of child care toward the death of a child refers to article 359 of the Criminal Code with the risk of a sentence of 5 years in prison.